Poetics of a literary text and traditions of national art words in Ukrainian literature of the XIX–XXI centuries (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article examines the theoretical level, the most significant concepts of the Ukrainian literary process, from the medieval-baroque times to the present. Also, on a theoretical level, outlined specific semantic and phenomenal, as applied to the general poetics of creation of a literary text, literary and figurative constants.
Keywords: poetics; literary creativity; concept; eloquence; poetry; transcendence; prose